![11x - ( - 3x - 4) = 3(5 - x) - 4 11x - ( - 3x - 4) = 3(5 - x) - 4](https://tex.z-dn.net/?f=11x+-+%28+-+3x+-+4%29+%3D+3%285+-+x%29+-+4)
Soluções para a tarefa
Respondido por
0
Resposta:
S={ 7/17}
Explicação passo-a-passo:
11x -( - 3x - 4) = 3.(5 - x) - 4
11x+3x+4=15-3x-4
14x+4=-3x+11
14x+3x=11-4
17x=7
x=7/17
Respondido por
0
Resposta:
11x - (-3x - 4) = 3(5 - x) - 4
11x + 3x + 4 = 15 - 3x - 4
17x = 7
x = 7/17
x = 0,411 (RESPOSTA)
Perguntas interessantes
Física,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Psicologia,
1 ano atrás
Geografia,
1 ano atrás